Determination of total purine and free purine content in milk, soymilk, and enteral nutritional supplements to assist nutritional therapy for hyperuricemia and gout. (2nd December 2022) - Fukuuchi, Tomoko; Itahashi, Itsuki; Takayanagi, Fukue; Yamaoka, Noriko; Kaneko, Kiyoko
Abstract: In this study, we determined the purine contents in milk and soymilk, as protein-rich drinks, and in enteral nutritional supplements employed to ameliorate protein malnutrition in the elderly. Milk consumption is known to lower serum uric acid levels and to promote uric acid excretion. However, discrepant results have been reported regarding the effect of soymilk on serum uric acid levels. The purpose of this study was to quantify and compare the total purine contents and the contents of individual purines and pyrimidines by molecular type (nucleotides, nucleosides, and bases).